ANALISIS PENGARUH IKLAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK AIR MINERAL - Rahman, Alliza Lia; Ferdiansyah, Ryan; Fauzi, Sulistia; Dewi, Verawati; Fathoni, Vika Rizky; Susilowati, Isnurrini Hidayat (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
Advertising is a form of promotion for a product or service, typically displayed in mass media such as television, newspapers, magazines, as well as on platforms like YouTube and social media, including Instagram, Facebook, and TikTok. This study was conducted to analyze the impact of promotional advertising on purchasing decisions for Aqua mineral water products. The population included all consumers who have seen Aqua advertisements on any media, such as television or other social media, and consumers who have purchased Aqua mineral water, totaling 70 respondents obtained through an online questionnaire distributed via Google Forms. The method applied is quantitative, analyzed using SPSS version 26. The variables tested include Promotion (X) and Purchase Decision (Y). Research instruments were validated through validity and reliability tests. The analysis techniques used include correlation and simple linear regression tests, encompassing t-tests and determination tests. The correlation test shows a strong and positive relationship between variables X and Y. The regression test produced the equation Y = 8.045 + 0.628X, indicating that the promotion variable significantly influences purchasing decisions for Aqua mineral water. This finding implies that the company should focus on enhancing promotion efforts to boost product purchasing decisions.